Prescription of antibiotics in Riga and Vilnius tertiary children's hospitals. Issue 4 (22nd March 2017) - Sviestina, Inese; Usonis, Vytautas; Gurksniene, Vilija; Burokiene, Sigita; Ivaskeviciene, Inga; Mozgis, Dzintars
Abstract : Objectives: The aim of this study was to compare the use of antibiotics among hospitalised children in Riga (Latvia) and in Vilnius (Lithuania) at two tertiary paediatric centres. Methods: A point prevalence survey (PPS) was conducted using validated and standardised Antibiotic Resistance and Prescribing in European Children (ARPEC) project methodology during November 2012. All inpatients less than 18 years old were included in the study. All data were recorded for patients with active antimicrobial prescriptions at 8 am on the day of the survey. Data were entered into the ARPEC-webPPS programme and were validated online for accuracy. Results: The proportion of patients receiving antimicrobial therapy was statistically different: 128 (37.0%) patients in Riga and 83 (26.3%) in Vilnius. The most common age group in Riga and Vilnius was 1–5 years. The most commonly used antibiotic classes for the treatment and prophylaxis of infection were third-generation cephalosporins (38; 25.5% prescriptions) in Riga and second-generation cephalosporins (16; 19.8%) in Vilnius. Parenteral use of antimicrobials was higher in Riga than in Vilnius: 111 (74.5%) prescriptions to paediatric patients in Riga and 45 (55.6%) prescriptions in Vilnius. Conclusions: The PPS identified differences in antibiotic use in both hospitals and problem areas for improvement: high use of third-generation cephalosporins for paediatric patients (in Riga) and predominant use of parenteral antibiotics. Further collaboration between both centres is needed because sharing audit data and antimicrobial stewardship initiatives may encourage further changes in practice at both institutions.